2017
DOI: 10.1126/scitranslmed.aag2285
|View full text |Cite
|
Sign up to set email alerts
|

Follicular CD8 T cells accumulate in HIV infection and can kill infected cells in vitro via bispecific antibodies

Abstract: Cytolytic CD8 T cells play a crucial role in the control and elimination of virus-infected cells and are a major focus of HIV cure efforts. However, it has been shown that HIV-specific CD8 T cells are infrequently found within germinal centers (GCs), a predominant site of active and latent HIV infection. We demonstrate that HIV infection induces marked changes in the phenotype, frequency, and localization of CD8 T cells within the lymph node (LN). Significantly increased frequencies of CD8 T cells in the B cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
197
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(218 citation statements)
references
References 60 publications
20
197
1
Order By: Relevance
“…These engineered constructs contain a broadly neutralizing antibody to HIV-1 Env linked to a monoclonal antibody to CD3. DARTS can mediate in vitro lysis of infected cells that are cultured with autologous CD8 + T cells (Sloan et al 2015; Petrovas et al 2017). Ex-vivo studies have also shown that DARTs can reduce viral outgrowth from the latent reservoir (Sung et al 2015b; Sung et al 2017).…”
Section: Directing the Immune Response To Effectively Target The Resementioning
confidence: 99%
See 2 more Smart Citations
“…These engineered constructs contain a broadly neutralizing antibody to HIV-1 Env linked to a monoclonal antibody to CD3. DARTS can mediate in vitro lysis of infected cells that are cultured with autologous CD8 + T cells (Sloan et al 2015; Petrovas et al 2017). Ex-vivo studies have also shown that DARTs can reduce viral outgrowth from the latent reservoir (Sung et al 2015b; Sung et al 2017).…”
Section: Directing the Immune Response To Effectively Target The Resementioning
confidence: 99%
“…However, even in the setting of minimal to absent persistent antigen, such as in individuals on suppressive cART, effector functions may not be completely restored. In the lymph node, for example, non-follicular and follicular CD8 + T cells express high levels of PD-1 and TIGIT, and blocking the PD-1/PDL-1 axis in vitro restores HIV-1-specific CD8 + T cell function in these cells (Petrovas et al 2017). Intriguingly, certain IC markers are also present on specific memory CD4 + T cells and are associated with higher HIV-1 DNA content, suggesting that these ICs somehow promote latency in these subsets (Chomont et al, 2009; Fromentin et al, 2016).…”
Section: Directing the Immune Response To Effectively Target The Resementioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, CXCR5 + CD8 + T cells from SIV-infected macaques (131) and HIV-infected patients (128) were found to eliminate virus-infected T FH cells when cocultured in vitro . Moreover, the anti-HIV activity of CXCR5 + CD8 + T cells from HIV-infected patients was significantly enhanced by a bispecific antibody (128).…”
Section: Tfh As a Hiv Reservoir In Cd4+ T Cellsmentioning
confidence: 99%
“…At present, the expression of PD-1 on CXCR5 + CD8 + T cells during viral infections remains controversial. Some studies (Im et al, 2016;Petrovas et al, 2017) reported high PD-1 expression on CXCR5 + CD8 + T cells compared to CXCR5-CD8 + T cells during chronic viral infections, whereas He et al (He et al, 2016) reported that CXCR5-CD8 + T cells expressed significantly lower levels of inhibitory molecules Tim-3 and PD-1 but higher levels of proinflammatory cytokines TNF-α and IFN-g.…”
Section: Introductionmentioning
confidence: 99%